Microbial Systems Ecology to Understand Cross-Feeding in Microbiomes - Mataigne, Victor; Vannier, Nathan; Vandenkoornhuyse, Philippe; Hacquard, Stéphane (Frontiers in Microbiology, 2021)
Understanding how microorganism-microorganism interactions shape microbial assemblages is a key to deciphering the evolution of dependencies and co-existence in complex microbiomes. Metabolic dependencies in cross-feeding exist in microbial communities and can at least partially determine microbial community composition. To parry the complexity and experimental limitations caused by the large number of possible interactions, new concepts from systems biology aim to decipher how the components of a system interact with each other. The idea that cross-feeding does impact microbiome assemblages has developed both theoretically and empirically, following a systems biology framework applied to microbial communities, formalized as microbial systems ecology and relying on integrated -omics data. This framework merges cellular and community scales and offers new avenues to untangle microbial coexistence primarily by metabolic modeling, one of the main approaches used for mechanistic studies. In this mini-review, we first give a concise explanation of microbial cross-feeding. We then discuss how microbial systems ecology can enable progress in microbial research. Finally, we provide an overview of a microbial systems ecology framework mostly based on genome-scale metabolic-network reconstruction that combines top-down and bottom-up approaches to assess the molecular mechanisms of deterministic processes of microbial community assembly, that is particularly suitable for use in synthetic biology and microbiome engineering.